Errors In Descriptive Text Written By The Ninth Grade Students Of SMP Negeri 2 Boyolali - Daryanto, Turut; , Prof. Dr. Endang Fauziati, M. Hum; , Drs. Maryadi, M.A (2013)
To err is man. But the errors they made must be dealt with. So as to my students in learning English, they committed many errors in writing descriptive text. It is because writing skill is not naturally acquired, but is gained by practice a lot. It needs expert's help to be a good writer. The proof is quite clear that not anyone can make a piece of writing in good organization even in his own language. It is his responsibility to help them cope with the difficulties. The writer is so concerned of the errors in his students' writing product of the descriptive text that he is interested to make a research on this problem and write a thesis. The objectives of this research are; 1. to describe the errors, 2. to trace the source of errors, 3. to know what most dominant errors, and 4. to know how frequent the errors occur. The data of this research is taken out from the composition of the descriptive text. I take 24 products out of 214 pieces. From the data source I found 294 sentences containing errors. Then I identify the errors based on the surface structure taxonomy; omission, addition, misformation, misordering, and blend. And the source of errors are caused by the strategy of language transfer and overgeneralization. It is quite natural that the students start thinking in their own language then they try to transfer the idea into English. Unfortunately, their L1 does not help much because English has different characteristics. most of the difference falls to the negative transfer. There are 2 kinds of transfer; vocabulary transfer and grammar transfer. The finding shows that the most frequent errors are on omission. There are 99 sentences containing omission (33.14%). The observation views this omission into 12 types. The second errors are on misformation. There are 78 sentences containing misformation (26.03%). The research finds 15 types of misformation. And the third rank is errors on blend. There are 61 sentences containing this problem (22.29%). This problem comprises 2 types of errors; diction/choice of words (lexicon). The forth big error is on addition. There are 48 sentences containing addition (15.49%). It is divided into 8 types. The least error is on misordering. There are 9 sentences (3.05%).